Respuesta :
f(x) = a - x
y = a - x
y + x = a - x + x
y + x = a
y + x - y = a - y
x = a - y
f-¹(x) = a - x
The inverse of a function is the opposite of the function.
See below for the proof of: [tex]\mathbf{f(x) = f^{-1}(x)}[/tex]
The function is given as:
[tex]\mathbf{f(x) = a - x}[/tex]
Rewrite as:
[tex]\mathbf{y = a - x}[/tex]
Swap x and y
[tex]\mathbf{x = a - y}[/tex]
Make y the subject
[tex]\mathbf{y = a - x}[/tex]
Rewrite as:
[tex]\mathbf{f^{-1}(x) = a - x}[/tex]
Hence:
[tex]\mathbf{f(x) = f^{-1}(x) = a - x}[/tex]
Read more about inverse functions at:
https://brainly.com/question/10300045